Comparison of intracuff alkalinized 2% lignocaine versus dexamethasone for attenuation of post operative laryngotracheal morbidity: a randomized comparative study - Rajbala; Sonali Beniwal; Mamta Khandelwal; T Mirthun Thomas (Journal of Applied Pharmaceutical Research, 2023)
Introduction: This randomized comparative study was planned to compare intracuff alkalinized lignocaine versus dexamethasone in preventing postoperative laryngotracheal morbidity. During general anesthesia patients were intubated with cuffed endotracheal tubes to provide effective positive pressure ventilation as well to prevent risk of aspiration. The cuffs of endotracheal tubes were inflated with air. This air in these cuffed endotracheal tubes can cause significant laryngotracheal morbidity. So, we planned this study to find a better substitute other than air to prevent postoperative laryngotracheal morbidity. Material and methods: Total 56 cases were taken. In group A, the cuff of the endotracheal tube was filled with 2% lignocaine 2 ml (40 mg) and sodium bicarbonate (NaHCO3 8.4%) 1 ml (total 3 ml volume). In Group B, the cuff of the endotracheal tube was filled with dexamethasone (8 mg) 2 ml with 1 ml NS (total 3 ml volume). Results: The incidence of sore throat and hoarseness was less in the alkalinized lignocaine group. (p value > 0.05). While the incidence of coughing was roughly similar in both groups and at different time intervals (P value >0.05). Conclusion: Intracuff alkalinized Lignocaine in comparison to intracuff dexamethasone causes less incidence of sore throat and hoarseness in post operative period thus improved patient comfort levels and better recovery profile.